Hubungan Pola Asuh Orang Tua Dengan Perilaku Sosial Anak Kelompok B Di TK Dharma Wanita Genengsari Kemusu Boyolali Tahun Ajaran 2015/2016 - PRASTIAWATI, MILA (2016)
ABSTRACT Mila Prastiawati/A520120022. RELATIONSHIP PARENTING PARENTS WITH CHILDREN GROUP B SOCIAL BEHAVIOR IN KINDERGARTEN DHARMA WANITA GENENGSARI KEMUSU BOYOLALI 2015/2016.Essay. The Faculty of Education, University of Muhammadiyah Surakarta. January, 2016. Background of this research is early childhood education is expected to optimize the potential of the child so that the need for a supportive environment in the educational process is the family environment children are educated in parenting different behaviors as diverse raised children while interacting and socializing in school. The purpose of this study was to determine the relationship between parenting parents with social behavior in group B TK Dharma Wanita Genengsari Kemusu Boyolali Academic Year 2015/2016. Research methods used in this study is descriptive correlational. Results of the research that has been conducted with a sample of 36 children in group B with a purposive sample using random sampling techniques. Data parenting parents obtained through questionnaires, while data on social behavior obtained through observation. The technique used by using product moment correlation. The analysis showed that parenting parents (X) has a significant relationship with the child's social behavior (Y). It can be seen from the results of data analysis showed > or 0.340> 0.329 at significance level of 0.05. If > then rejected to test the hypothesis about parenting parents (questionnaire) with social behavior (observation) connection. It can be concluded that there is a relationship between parenting parents with children in kindergarten social behavior Dharma Wanita Genengsari Kemusu Boyolali Academic Year 2015/2016. Keywords: Parenting Parents, Child Social Behavior